Optimasi Aspek Pemasaran Digital dan Keuangan Dalam Mengembangkan Potensi Desa Wisata Edukasi Glempang - Rifqoh Juliandika Putra; Liana Mizanatul Maulia; Farah Tsabitah; Ardhia Rahmahayati; Citra Hapsari Maharani; Febryansyah Pratama Gusti; Iran Nilam Anjani; Eliza Nazilul Falah; Ascaryan Rafinda; Najmudin Najmudin (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
The priority objective of this activity is to increase understanding, awareness, and skills for tourism managers, Pokdarwis, and MSME actors regarding digital marketing, product content, and financial reports through optimizing the promotion and marketing of tourism objects. Glempang Village is an educational tourism village with its flagship tourism, namely Keleen Kali which is intended for children aged 5 years to 10 years. In addition, there are also MSME supporting the economy of citizens and natural tourism such as waterfalls. With this potential sources, However, Glempang Village is still not enough to optimize, especially in terms of digitalization and financial management. There are still many human resources that don’t understand about the progress of tourism and MSME so that there is a need for assistance and a digital marketing training, making video and interesting photos, as well as making simple financial reports for MSME actors. Training activities with optimization of tourism villages should be carried out periodically in terms of facilities, promotion, and marketing by maximizing the potential of human resources who are still in the productive age.